2006
DOI: 10.1007/s00213-006-0541-x
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular aripiprazole for the treatment of acute agitation in patients with schizophrenia or schizoaffective disorder: a double-blind, placebo-controlled comparison with intramuscular haloperidol

Abstract: These results show that IM aripiprazole is an effective treatment, comparable to IM haloperidol, and well-tolerated for acute agitation in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
3
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 26 publications
0
71
3
6
Order By: Relevance
“…10,37 Moreover, other studies have not consistently demonstrated the superior efficacy of SGA compared to haloperidol alone. 35,[38][39][40] Our results demonstrated that olanzapine required fewer additional medications, which was different from the results of the TREC study. 4 Some clinical trials among patients with acute agitation associated with schizophrenia have demonstrated that the IM formulations of atypical antipsychotics provide similar efficacy to those of conventional antipsychotics, albeit without the associated high incidence of extra-pyramidal side effects (EPS).…”
Section: Discussioncontrasting
confidence: 99%
“…10,37 Moreover, other studies have not consistently demonstrated the superior efficacy of SGA compared to haloperidol alone. 35,[38][39][40] Our results demonstrated that olanzapine required fewer additional medications, which was different from the results of the TREC study. 4 Some clinical trials among patients with acute agitation associated with schizophrenia have demonstrated that the IM formulations of atypical antipsychotics provide similar efficacy to those of conventional antipsychotics, albeit without the associated high incidence of extra-pyramidal side effects (EPS).…”
Section: Discussioncontrasting
confidence: 99%
“…In at least three randomised, double-blind, placebo-controlled studies it was found to be efficacious, safe and tolerable in treating agitation in patients with bipolar I disorder, schizophrenia or schizoaffective disorder (Andrezina 2006;Currier 2007;Tran-Johnson 2007). In one of these studies (Andrezina 2006) the efficacy of 9.75 mg intramuscular aripiprazole was established v. 6.5 mg intramuscular haloperidol. Aripiprazole demonstrated rapid and effective control of agitation in schizophrenia and schizoaffective disorder with a significant reduction in events involving extrapyramidal side-effects (1.7% v. 12.6%) (Citrome 2007).…”
Section: Aripiprazolementioning
confidence: 99%
“…We can recognize and keep clear in our minds that we do treat some patients before we are certain of their diagnosis. Careful consideration of a given patient's diagnostic possibilities allows careful choice of treatment, even if it is a combination of drugs (Alexander et al 2004 ;Allen et al 2005 ;Andrezina et al 2006 ;Battaglia et al 1997 ;Breier et al 2002 ;Breitbart et al 1996 ;Broderick et al 2002 ;Brook et …”
Section: So-called Agitated Patientsmentioning
confidence: 99%